Interactions investigated by the spectroscopic, microscopic and molecular docking studies for liquid crystal-based biosensor. Issue 3 (19th February 2022) - Kalita, Priyanki; Singh, Ranjan K; Bhattacharjee, Ayon
ABSTRACT: The interactions between liquid crystal (LC) 4´-pentyl-4-biphenylcarbonitrile and protein bovine serum albumin are investigated to develop an LC-based biosensor. Various techniques, such as polarising optical microscopy, Raman spectroscopy, and molecular docking method, are used for analysing these interactions. The change in the alignment of LC molecules in the presence of bovine serum albumin results in the director configuration transition. This transfiguration of the director of LC molecules, when it undergoes a change from radial to bipolar configuration, confirms the detection of albumins under polarising optical microscopy. The limit of detection is also determined from this study. The Raman spectra are deconvoluted to calculate the spectral parameters, namely peak position, linewidth, and integrated intensity. The variation of these parameters with concentration and temperature is discussed, pertaining to the changes in orientational ordering and inter/intramolecular interactions. The active binding sites, active residues and binding energy are calculated by molecular docking analysis. The active binding residues of albumins involved in the docking with liquid crystal are further confirmed using Raman spectroscopy. Graphical Abstract: uf0001